Models of the information system for managing educational processes in distance and traditional forms of education in higher educational institutions - Джаббаров, Адиб; Mahmanov, Orif (MMIT Proceedings, 2025)
This article analyzes effective models of information systems for managing educational processes in distance and traditional forms of education in higher educational institutions. On the example of INTI (Malaysia) and TIUE (Uzbekistan) universities, mechanisms for digitalization, automation of educational processes, and monitoring of the activities of students and teachers are studied. The research results reveal the possibilities of improving the quality of education, implementing an individual approach and innovative pedagogical solutions.